Propheten der Epochen = Prophets during the Epochs : Festschrift für István Karasszon zum 60. Geburtstag - Kókai Nagy, Viktor; Karasszon, István; Egeresi, László Sándor (Alter Orient und Altes Testament, 2015)
Prophet voice: silence shattered from 'elsewhere' -- Saul unter den Propheten -- Amos 1,1 und die Stratigraphie der eisenzeitlichen Ortslagen in Galiläa -- Amos und die Weisheit -- Die Visionen des Amosbuches -- "Call a scribe!": Amos7:10-11 and ancient Near Eastern prophetic letters -- Jesaja und das Refaim-Tal. Erwägungen zu Jes 17, 4-6 -- The story of Isaiah with his King. The role of the Hezekiah Narratives in 1-2 Kings and in Isaiah -- Reconsidering Habakkuk 1:8 -- The Uriah case (Jeremiah 26:20-23) -- Moses: The suffering prophet in Deuteronomy and Psalm 90-92 -- "Steinigt den störrischen Sohn!" - "Geisselt die Ehebrecher!" Überlegungen zum Sinn von "problematischen "Geboten in der biblischen und der koranischen Überlieferung -- Ezechiel 18: Folgen des Handelns früherer Generationen und eigene Verantwortung -- Concepts of transgression and restoration in Ezekiel and Malachi with special attention to the cult. An intertextual suvey -- Kritik der reinen Vernunft. Die hermeneutische Funktion der Prophetie im Hiobbuch -- Prophetic legitimation (and de-legitimation) in the Persian period against its ancient Near Eastern background -- The figure of Daniel in late antique synagogue art -- Die Propheten und die religiösen Gemeinschaften bei Josphus -- Shifts in the paradigm. Past and future of teaching classical Hebrew in Hungary